2014
DOI: 10.5897/jbr2013.0122
|View full text |Cite
|
Sign up to set email alerts
|

Detection of biofilm formation of a collection of fifty strains of Staphylococcus aureus isolated in Algeria at the University Hospital of Tlemcen

Abstract: The burden of disease caused by Staphylococcus aureus continues to grow; this organism has the ability to form biofilm and it is also a frequent cause of medical device and implant-related infections. The objective of this study was to evaluate the biofilm-forming ability of a collection of clinical isolates of S. aureus. In a total of 240 Staphylococcus spp. isolated from catheters, retrieved at five services (neonatology, internal medicine, pneumology, pediatric and neurology), only 50 (20.83%) strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…[21, 26]. It has been reported that more than 65% of all bacterial infections are related to biofilm production; however, it also depends on the type of the infection and etiology [27]. Previous studies have also highlighted the role of biofilm formation in UTI [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…[21, 26]. It has been reported that more than 65% of all bacterial infections are related to biofilm production; however, it also depends on the type of the infection and etiology [27]. Previous studies have also highlighted the role of biofilm formation in UTI [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic foot wound patients with S. aureus colonization have a 2-fold increase in healing time [17]. Biofilm protection of microorganisms from opsonophagocytosis and antibiotics make S. aureus capable of causing chronic infection and sepsis an economically important organism in nosocomial infections [18].…”
Section: Introductionmentioning
confidence: 99%
“…3 U n c o r r e c t e d P r o o f (36.7%) strains produced no biofilm. Other studies have reported a slightly higher number of biofilm producers among Staphylococcal species (23,29). In the CRA method, biofilm formation was observed in 80 (81.6%) isolates whereas 17 (17.3%) strains did not show any biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The OD cut-off value was separately calculated for each Microtiter plate. Biofilm formation by isolates was calculated and categorized according to the absorbance of the crystal violetstained attached cells (23,24) (Table 2).…”
Section: Microtiter Plate Assay (Mtp)mentioning
confidence: 99%